PHILOSOPHICAL VALUES OF ISLAMIC PHILANTHROPY IN STRENGTHENING WELFARE: A CASE STUDY OF ZAKAT MANAGEMENT AT BAZNAS - Boedi Satria; Syukri Iska; Hashim Bin Ahmad Shiyuti (JURNAL PROFIT, 2026)
Islamic philanthropy plays a strategic role in supporting social welfare and poverty alleviation through the instrument of zakat, which is based on philosophical values. However, the implementation of these values often varies between institutions, thus requiring an in-depth study in a local context. This research aims to analyze the application of the philosophical values of Islamic philanthropy, including justice, trustworthiness, brotherhood, balance, and public interest, as well as the role of zakat in improving the welfare of mustahik at BAZNAS Pariaman city. The method used is a qualitative approach with a case study design through observation, in-depth interviews, and documentation. The results show that BAZNAS Kota Pariaman not only applies professional governance through mustahik verification, routine audits, and the utilization of various fundraising channels, but also emphasizes spiritual values in the development of mustahik and public services. The discussion reveals that philanthropic practices in this institution are in line with previous research emphasizing the importance of integrating the values of justice, trustworthiness, and public interest in the effectiveness of zakat programs. In conclusion, BAZNAS Pariaman city has successfully implemented the philosophical values of Islamic philanthropy comprehensively, thereby providing material and spiritual impacts for beneficiaries and strengthening public trust.